Contrast-enhanced mammography in the evaluation of breast calcifications: preliminary experience. Issue 6 (December 2020) - Depretto, Catherine; Borelli, Anna; Liguori, Alessandro; Presti, Gabriele; Vingiani, Andrea; Cartia, Francesco; Ferranti, Claudio; Scaperrotta, Gianfranco P.
Aim: To evaluate the presence of contrast enhancement at the site of calcifications on contrast-enhanced mammography (CEM) and histopathologic results at vacuum-assisted biopsy (VAB), and to examine the association with lesion size and immunohistochemical characteristics, in order to assess disease aggressiveness in malignant lesions. Methods: A total of 34 patients with 36 clusters of suspicious calcifications (BI-RADS 4) were investigated with CEM before the scheduled VAB. We evaluated the presence or absence of enhancement, histologic diagnosis, and, in case of malignant lesions, their size and the expression of Ki-67. Results: In our case series, 15/36 (41.7%) lesions were malignant. In 7 cases, contrast enhancement was found at the site of calcifications. Data about size of lesions and immunohistochemical characterization were not available for all malignant cases. In 5 cases with CEM enhancement, all lesions were >5 mm and overexpressing Ki-67 (>20%); in 6 cases with no contrast enhancement, the lesions were <5 mm and with low Ki-67 values (<20%). Conclusion: Our preliminary study provides indications on the ability of CEM to recognize neoplasms larger than 5 mm, with high proliferative index (Ki-67 >20%), and frequently human epidermal growth factor receptor 2–positive. Our preliminary results suggest that CEM could detect aggressive malignancies. This could be the starting point for planning further studies with larger numbers of cases, in an attempt to reduce overdiagnosis and consequent overtreatment.